Trophic ecology of Girardinichthys multiradiatus (Pisces: Goodeidae) in two dams in the state of Mexico - Cruz-Gómez, Adolfo (2024)
In this work, the feeding results of Girardinichthys multiradiatus (Meek, 1904) in the dams El Molino and Brockman in the State of Mexico, Mexico during the dry and rainy climatic seasons were analyzed. Th e fi sh were collected with a baitwell net, 279 organisms from the El Molino dam and 375 from the Brockman dam, from which both males and females were selected to carry out the analysis of the stomach contents, obtaining the trophic spectrum, the niche amplitude according to Levin Index and the food importance index using the Zander Index. Th e results showed 19 types of food consumed, 14 in El Molino and 18 in Brockman, with cladocerans, copepods, and Diptera being the most consumed in both systems. According to Zander’s index, Diptera and gastropods were essential prey at Brockman Dam, while cladocerans and Diptera were essential prey at El Molino. According to Levin, the niche amplitude was low, so it is considered a specialist. Th is species is carnivorous and the results show variations in its diet between the two systems studied, so by applying a Non-Metric Multidimensional Scaling (N-MDS) analysis it was demonstrated that there is a diff erential food consumption between the two systems and climatic seasons within each site, which makes it necessary to carry out more studies on the diet of G. multiradiatus in the environments of the State of Mexico to know its status as well as the use and selectivity of the resources in the environments where this species is distributed.